Marine and Terrestrial Organic Ice-Nucleating Particles in Pristine Marine to Continentally Influenced Northeast Atlantic Air Masses - Zamin A. Kanji; Colin D. O'Dowd; Franco Belosi; Ulrike Lohmann; Thomas C. J. Hill; Salvatore Marullo; Matteo Rinaldi; Jurgita Ovadnevaite; James Atkinson; Christina S. McCluskey; Paul J. DeMott; Sonia M. Kreidenweis; et al. (Journal of Geophysical Research: Atmospheres, 2018)
AbstractSea spray aerosol (SSA) generated by bubble bursting at the ocean surface is an important component of aerosol‐cloud interactions over remote oceans, providing the atmosphere with ice‐nucleating particles (INPs) or particles required for heterogeneous ice nucleation. Studies have shown that organic INPs are emitted during phytoplankton blooms, but changes in INP number concentrations (nINPs) due to ocean biological activity have not been directly demonstrated in natural SSA. In this study, a clean sector sampler was used to differentiate ice nucleation and composition of pristine SSA from terrestrial aerosol at the Mace Head Research Station in August 2015. Average nINPs active at −15 °C (nINPs,−15 °C) were 0.0011 L−1, and large variability (up to a factor of 200) was observed for INPs active warmer than −22 °C. Highest nINPs in the clean sector occurred during a period of elevated marine organic aerosol from offshore biological activity (M1, nINPs,−15 °C = 0.0077 L−1). A peak in nINPs was also observed in terrestrial organic aerosol (T1, nINPs,−15 °C = 0.0076 L−1). The impacts of heating and hydrogen peroxide digestion on nINPs indicate that INPs at Mace Head Research Station were largely organic and that INPs observed during M1 and T1 were biological (i.e., protein containing). Complexities of predicting increases in nINPs due to offshore biological activity are explored. A parameterization for pristine SSA INPs over the North Atlantic Ocean was developed, illustrating that SSA is associated with a factor of 1,000 fewer ice‐nucleating sites per surface area of aerosol compared to mineral dust.